"You feel like you're part of something bigger": exploring motivations for community garden participation in Melbourne, Australia - Jonathan Kingsley; Emily Foenander; Aisling Bailey (BMC, 2019)
Abstract Background Increased global urbanisation has led to public health challenges. Community gardens are identified as a mechanism for addressing socio-ecological determinants of health. This study aims to explore motives for joining community gardens, and the extent to which participation can be facilitated given barriers and enablers to community gardening. Such a study fills a gap in the public health literature, particularly in the Australian context. Methods This paper presents findings from semi-structured interviews with 23 participants from 6 community gardens across Melbourne. Applying phenomenological, epistemological and reflexive methodologies and thematic analysis of the data, this study provides a snapshot of drivers of community garden participation. Results Results were categorised into six enabling themes to participation. These themes revolved around (i) family history, childhood and passion for gardening; (ii) productive gardening, sustainability and growing fresh produce in nature; (iii) building social and community connections; (iv) community and civic action; (v) stress relief; and (vi) building identity, pride and purpose. Time costs incurred, garden governance and vandalism of garden spaces were among the barriers to community garden participation. Conclusion Although an interest in the act of gardening itself may be universally present among community gardeners to varying degrees, the findings of this study suggest that motivations for participation are diverse and span a range of ancestral, social, environmental, and political domains. This study contributes exploratory insights on community garden motivations and sustained involvement across multiple urban sites in Melbourne (Australia). This study recommends extending this work by undertaking future quantitative research that can move from local case studies to a national guidelines on how to engage more people in urban agriculture activities like community gardening.